2023
DOI: 10.1007/s13555-023-00998-w
|View full text |Cite
|
Sign up to set email alerts
|

A Propensity Score-Matched Study on the Changes of TB Status and TB-IGRA Values in Patients with Psoriasis with Latent TB Receiving Secukinumab

Yue Xiao,
Wenyao Mi,
Jinqiu Wang
et al.

Abstract: Introduction The utilization of biologics in patients with psoriasis with latent tuberculosis infection (LTBI) has garnered significant attention. Although the tuberculosis (TB) safety profile of second-generation biologics, including secukinumab, has been partially confirmed in both clinical trials and real-world studies, the necessity for prophylactic therapy in patients with LTBI prior to administering this class of biologics remains a topic of controversy. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Segueni et al found minimal changes in the transcriptomic levels of Il17 and Il23a in M. tuberculosis -infected mice, indicating a limited role for IL-17 pathways in controlling tuberculosis infection [ 11 ]. Shu et al and Xiao et al observed no ATB cases among patients with psoriasis and TBI treated with secukinumab without TPT over median follow-up of 52 weeks and 23 months, respectively [ 17 , 18 ]. Our study, with a larger sample size and longer follow-up duration, strengthens these consistent findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Segueni et al found minimal changes in the transcriptomic levels of Il17 and Il23a in M. tuberculosis -infected mice, indicating a limited role for IL-17 pathways in controlling tuberculosis infection [ 11 ]. Shu et al and Xiao et al observed no ATB cases among patients with psoriasis and TBI treated with secukinumab without TPT over median follow-up of 52 weeks and 23 months, respectively [ 17 , 18 ]. Our study, with a larger sample size and longer follow-up duration, strengthens these consistent findings.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, QFT dynamics appear to be poorly correlated with the risk of ATB development [ 22 ]. A recent propensity score-matched study found no significant differences in QFT values before and after secukinumab treatment in patients with psoriasis and TBI for both the TPT and non-TPT groups [ 17 ]. Given these findings, continuous IGRA monitoring may not be essential for patients with psoriasis and TBI on IL-17A inhibitor therapy.…”
Section: Discussionmentioning
confidence: 99%